Copper Sulfide/N,S-Doped Carbon Nanocomposites as High-Performance Supercapacitor Devices - Yeganeh Ghotbi M.; Sikiru S.O.; Ansari M.N.M.; Soleimani H.; Kou L.; Song J. (American Chemical Society, 2025)
Batteries and supercapacitors (SCs) are energy storage devices that are more efficient, smaller, lighter, and capable of storing greater amounts of energy, thereby meeting the higher energy storage requirements of the modern world. However, real-world commercial carbon-based SCs face the persistent challenge of relatively low energy density and capacity. To address this, researchers have investigated strategies such as doping carbon materials with heteroatoms and hybridizing or combining carbon with specific metal compounds. In this study, a novel copper ferrocyanide/sulfide/N,S-doped carbon nanocomposite was developed by using a copper hydroxide ferrocyanide nanohybrid as a precursor. The copper phases were selectively removed through an acid etching process. High-resolution transmission electron microscopy and X-ray photoelectron spectroscopy analyses confirmed the structure and chemical bonding in the resulting materials. These nanocomposites and doped carbon materials were used as active components in supercapacitor electrodes. A commercial-like symmetric SC device was then fabricated by using N,S-doped carbon nanosheets and an organic commercial electrolyte. The device exhibited a high capacitance of 33 F/g, an energy density of 41 Wh/kg, and a power density of 1500 W/kg using a conventional slow charge-discharge approach. It also demonstrated a capacitance retention of over 90% after 1000 cycles in a fast charge approach. ? 2024 American Chemical Society.